Human Liver Cells Expressing Albumin and Mesenchymal Characteristics Give Rise to Insulin-Producing Cells - Irit Meivar-Levy; Tamar Sapir; Dana Berneman; Tal Weissbach; Sylvie Polak-Charcon; Philippe Ravassard; Andreas G. Tzakis; Eytan Mor; Camillo Ricordi; Sarah Ferber (Journal of Transplantation)
Activation of the pancreatic lineage in the liver has been suggested as a potential autologous cell replacement therapy for diabetic patients. Transcription factors-induced liver-to-pancreas reprogramming has been demonstrated in numerous species both in vivo and in vitro. However, human-derived liver cells capable of acquiring the alternate pancreatic repertoire have never been characterized. It is yet unknown whether hepatic-like stem cells or rather adult liver cells give rise to insulin-producing cells. Using an in vitro experimental system, we demonstrate that proliferating adherent human liver cells acquire mesenchymal-like characteristics and a considerable level of cellular plasticity. However, using a lineage-tracing approach, we demonstrate that insulin-producing cells are primarily generated in cells enriched for adult hepatic markers that coexpress both albumin and mesenchymal markers. Taken together, our data suggest that adult human hepatic tissue retains a substantial level of developmental plasticity, which could be exploited in regenerative medicine approaches.